2007
DOI: 10.4037/ccn2007.27.5.12
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating the Retention of Experienced: Critical Care Nurses: A Survey Report on What Matters Most

Abstract: If healthcare facilities are ... interested in retaining their ... nurses, [they should enable] these nurses to not only plan their work and time off, but [ensure] that those schedules are implemented on a reliable basis. The Editorial 1 in the April 2007 issue of Critical Care Nurse addressed the topic of how experienced critical care nurses might be retained within the profession, summarized existing strategies proposed from literature and discourse on this topic, and invited readers to complete a brief onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…1997, Boyle et al. 1999, Alspach 2007, Herrin & Spears 2007). Therefore, strategies need to be developed to address the management‐related issues in the ED.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1997, Boyle et al. 1999, Alspach 2007, Herrin & Spears 2007). Therefore, strategies need to be developed to address the management‐related issues in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is no question that staffing/resource adequacy and scheduling are pervasive issues for nurses (Alspach 2007). However, while several researchers have reported that organizational respect and compassionate, competent, honest and ethical managers, were among the most significant factors for retaining critical care nurses (Fang 2001, Alspach 2007), TzengÕs (2002 findings suggested that leadership style had no impact on job satisfaction or intention to leave. In a relatively large study of organizational climate and intention to leave in ICU nurses (n = 2323), Stone et al (2006) found that only professional practice and competence were independently and inversely related to intention to leave.…”
Section: Influencing Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…). Given that retention is influenced by many factors such as flexible scheduling, money, health benefits, mentorship opportunities, organisational focus on retention, management practices and recognition, work environment and retirement plans, the results of this review do not point to one particular intervention that could be implemented to influence experienced nurse retention (Force , Alspach , Hirschkorn et al . ).…”
Section: Discussionmentioning
confidence: 99%